Targeted muscle reinnervation prevents and reverses rat pain behaviors after nerve transection. Issue 2 (25th May 2022) - Roth, Elizabeth; Linehan, Allison; Weihrauch, Dorothee; Stucky, Cheryl; Hogan, Quinn; Hoben, Gwendolyn
Abstract : Supplemental Digital Content is Available in the Text. Targeted muscle reinnervation in the spared nerve injury model recapitulates clinical successes and further supports the relationship of nerve regeneration and reinnervation in neuropathic pain. Abstract: Targeted muscle reinnervation (TMR) is a clinical intervention that is rapidly becoming common in major limb amputation to prevent or reduce amputation-related pain. However, TMR is much less effective when applied long after injury compared with acute TMR. Since the mechanisms governing pain relief in TMR of amputated nerves are unknown, we developed a preclinical model as a platform for mechanistic examination. Following spared nerve injury (SNI), rats underwent either TMR, simple neuroma excision, or a sham manipulation of the injury site. These interventions were performed immediately or delayed (3 or 12 weeks) after SNI. Pain behavior was measured as sensitivity to mechanical stimuli (pin, von Frey, and dynamic brush) and thermal stimuli (acetone and radiant heat). Spared nerve injury produced hypersensitivity to all mechanical stimuli and cold, which persisted after sham surgery. Targeted muscle reinnervation at the time of SNI prevented the development of pain behaviors and performing TMR 3 weeks after SNI reversed pain behaviors to baseline. By contrast, TMR performed at 12 weeks after SNI had no effect on pain behaviors. Neuroma excision resulted in significantly less reduction in hyperalgesia compared with TMR when performed 3 weeks after SNI but had no effect at 12 weeks after SNI. In this model, the pain phenotype induced by nerve transection is reduced by TMR when performed within 3 weeks after injury. However, TMR delayed 12 weeks after injury fails to reduce pain behaviors. This replicates clinical experience with limb amputation, supporting validity of this model for examining the mechanisms of TMR analgesia.